Access to Basic HIV-Related Services and PrEP Acceptability among Men Who Have sex with Men Worldwide: Barriers, Facilitators, and Implications for Combination Prevention. (8th July 2013) - Ayala, George; Makofane, Keletso; Santos, Glenn-Milo; Beck, Jack; Do, Tri D.; Hebert, Pato; Wilson, Patrick A.; Pyun, Thomas; Arreola, Sonya
Abstract : Introduction . Men who have sex with men (MSM) are disproportionately impacted by HIV globally. Easily accessible combination HIV prevention strategies, tailored to the needs of MSM, are needed to effectively address the AIDS pandemic. Methods and Materials . We conducted a cross-sectional study among MSM (n = 3748 ) from 145 countries from April to August 2012. Using multivariable random effects models, we examined factors associated with acceptability of preexposure prophylaxis (PrEP) and access to condoms, lubricants, HIV testing, and HIV treatment. Results . Condoms and lubricants were accessible to 35% and 22% of all respondents, respectively. HIV testing was accessible to 35% of HIV-negative respondents. Forty-three percent of all HIV-positive respondents reported that antiretroviral therapy was easily accessible. Homophobia, outness, and service provider stigma were significantly associated with reduced access to services. Conversely, community engagement, connection to gay community, and comfort with service providers were associated with increased access. PrEP acceptability was associated with lower PrEP-related stigma, less knowledge about PrEP, less outness, higher service provider stigma, and having experienced violence for being MSM. Conclusions . Ensuring HIV service access among MSM will be critical in maximizing the potential effectiveness of combination approaches, especially given the interdependence of both basic and newer interventions like PrEP. Barriers and facilitators of HIV service access for MSM should be better understood and addressed.